Hemp as A Sustainable Carbon Negative Plant: A Review of Its Properties, Applications, Challenges and Future Directions - Nitin Muttil; Sayaad Sadath; Darren Coughlan; Prudvireddy Paresi; Swadesh Kumar Singh (International Journal of Integrated Engineering, 2024)
Hemp is a versatile plant from the Cannabis sativa species, that has gained significant attention in recent years due to its potential to contribute to sustainable development and climate change mitigation. Hemp has the remarkable ability to absorb and store carbon dioxide not just during its growth phase, but also during its application and thus has the potential to be carbon negative. With the alarming global increase in carbon emissions and its implications, the cultivation and application of hemp can be a valuable tool in mitigating climate change. Although hemp is a versatile plant with many countries like Canada and China leading the way in its cultivation, it still faces challenges in Australia in terms of its acceptance, cultivation and widespread application. Much more needs to be done in terms of gaining a better understanding of the potential of hemp, growth opportunities, future prospects and challenges in further developing the industry. This review paper aims to provide a comprehensive overview of hemp’s properties, applications, challenges, and future directions in the context of its role as a sustainable carbon-negative plant. The review begins by exploring the unique properties of hemp that make it an ideal candidate for carbon sequestration. The review also examines the diverse range of applications for hemp across multiple industries, ranging from construction materials, paper and packaging to biofuels and edible oil. The review has also identified several challenges and barriers to hemp’s widespread adoption as a sustainable carbon-negative plant